(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Context: The accumulation of extracellular matrix components, especially elastic fibers and collagen, causes liver fibrosis to worsen over time, causing the organ to stop working as it should. In order to diagnose, predict, and treat fibrosis, accurate histological staging is required. Common fibrosis evaluation stains include hematoxylin and eosin (H and E), Masson’s trichrome (MT), and orcein (OR), although there is a lack of clarity about the relative efficacy and connection of these stains in everyday practice. Approach: From 2021 to 2023, 76 liver biopsy samples were reviewed in this retrospective analysis. The patients were sent to Taleghani Hospital in Tehran, Iran. We stained all of the samples with H&E, MT, and OR. Skilled pathologists staged the fibrosis using the Ishak grading method. The agreement and correlation between staining procedures were evaluated using statistical analysis, which included Fisher’s exact test. Significant results were defined as P values less than 0.05. The results show that with 76 patients (34.2% male, mean age 41.2 years), the finding of fibrosis was most common at Stage 2 for MT (35.5%) and Stage 3 for OR (23.7%). H and E and MT showed significant differences in fibrosis staging (P < 0.001), as with MT and OR (P = 0.006). At Stage 2, there was a significant difference between MT and OR (P = 0.003). Importantly, in 36.8% of instances, OR staining revealed a lower level than MT, but in 23.7% of cases, OR staining revealed a higher stage. When looking at individuals between the ages of 0 and 32 (P = 0.032) and males (P = 0.036), there were statistically significant differences between MT and OR. In summary: In order to evaluate liver fibrosis, our results show that MT and OR staining techniques provide complementing information. The noticeable differences, particularly in the intermediate phases, indicate that OR staining, when used in conjunction with MT, improves diagnostic precision. For a thorough assessment of fibrosis in liver biopsies, it is advised to routinely utilize both stains.